"Efecto del quitosano en dieta sobre la repuesta productiva y he,atològica de alevines de tilapia roja (Oreochromis sp.)" - Pacheco Morales, Ginger Karina (2020)
The research was carried out at the “La María” Campus, belonging to the State Technical University of Quevedo, located at kilometer 7½ of the Quevedo - El Empalme road. The investigation lasted 55 days. Three experimental diets were used, including 0%, 2% and 4% chitosan in red tilapia fry. The objective of the work was: To evaluate the effect of chitosan in diets on the productive and hematological response of red tilapia fry (Oreochromis sp.). A completely randomized design (DCA) was applied, for three treatments with three repetitions (experimental tanks) with a density of 15 fry / tank. Prior to the analyzes, let's verify the tests of normality and homocedasticity to the data selected in the variables. The results of the variable zootechnical parameters significant difference (P ≤ 0.05) between T3 (4% chitosan inclusion) with respect to T1 (0% chitosan inclusion) in the variables of final weight, final height, weight gain, weight gain. The T3 obtained a 100% survival rate. Regarding nutritional parameters such as the rate of food conversion and food efficiency statistically, there were highly variable differences between T3 and T1, with the best nutritional values being T3 for both variables. On the other hand, the hematological variables evaluated as glucose and cholesterol were analyzed by the inclusion of chitosan in the diet, T3 obtained the lowest values compared to T1, as for the triglyceride variable there were no statistical differences between T3 and T1. This study shows that the inclusion of chitosan had a positive effect on the parameters studied, being an ideal product that could be determined in different animal productions. Keywords: hematological, inclusion, nutrition, chitosan, zootechnical.